Uji Lapangan Respon Tanaman Padi Sawah dengan Pupuk NPK Compaction DGW di Kelurahan Taratara Satu, Kecamatan Tomohon Barat, Kota Tomohon - Kamagi, Yani Ezrah Bartolomeus; Pioh, Diane Debie; Kawulusan, Rafli Irland; Azizah, Futihatu Rizkiani; Kumolontang, Wiesje Junnieke Nathsuo; Indrasari, Silfi (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2026)
Rice (Oryza sativa L.) has become one of the main food crops in Indonesia. Rice productivity plays an important role for the supply of the community on a national scale. The application of NPK fertilizer can be a solution. The objective of this study was to determine the response of NPK compound fertilizer “Compaction DGW” on rice yield. The experimental was design using a Randomized Block Design (RBD) that consisted of 3 treatments and 3 replications, on 2,5 m x 4 m (10 m2) plot. The NPK compound fertilizer used for this study was “Compaction DGW”. The treatments included K0 (control), A2B1 (200kg of NPK fertilizer + fertilizer grain size > 1 mm), and A2B2 (200 kg/ha NPK fertilizer + fertilizer grain size < 1 mm). The variable observed was the production of dry grain. The results showed that the application of NPK compound fertilizer “Compaction DGW” with grain size >1mm and <1mm had no significant effect on increasing the dry grain weight. However, NPK compound fertilizer “Compaction DGW” produced higher dry grain weight compared to the control.